UPACARA PEMASUPATIAN PAICA DI PURA TELAGASARI DESA JINENGDALEM KECAMATAN BULELENG KABUPATEN BULELENG (KAJIAN BENTUK, FUNGSI, MAKNA) - Ketut Agus Nova (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2018)
The Paica Pengupatian ceremony procession at Telagasari Temple in JinengdalemVillage was carried out preceded by determining the people in charge of bringing Paica Ida Bhatara to the stakeholders or people who had been mawinten or purified. The ceremony is held every Monday at Kengwon Enjitan every year. The implementation of large ceremonies sets five years and regular ceremonies once a year. The ceremony was preceded by the preparation of facilities a few days earlier. The people do ngayah make offerings and other facilities. On the day of the implementation of Paica ida Bhatara was revealed with a piuning ceremony, then sprinkled with water until basan. Furthermore, the people who brought Paica surrounded the entire palinggih or sanggah in Pura Telagasari three times. After that, it is placed in front of the palinggih in front of the bison made of bamboo for one night until the next day. The ummah carried out Jagra / mekemit until morning, then after morning paica was put back in its original place.